Cell- and subcellular organelle-targeting nanoparticle-mediated breast cancer therapy - Wei, Xue; Yang, Ming (Frontiers in Pharmacology, 2023)
Breast cancer (BC) is the most prevalence malignant tumor, surpassing lung cancer as the most frequent malignancy in women. Drug resistance, metastasis, and immune escape are the major factors affecting patient survival and represent a huge challenge in BC treatment in clinic. The cell- and subcellular organelle-targeting nanoparticles-mediated targeted BC therapy may be an effective modality for immune evasion, metastasis, and drug resistance. Nanocarriers, efficiently delivering small molecular and macromolecules, are used to target subcellular apparatuses with excellent targeting, controlled delivery, and fewer side effects. This study summarizes and critically analyzes the latest nanoparticle-mediated subcellular targeted therapeutic based on chemotherapy, gene, immunotherapy, and combination therapy in detail, and discusses the challenges and opportunities of nanoparticle therapy.